Vincent Ventura and the Curse of the Donkey Lady - Garza, Xavier (Piñata Books, Arte Público Press, 2024)
Vincent Ventura returns in the sixth installment of the bilingual Monster Fighter Mystery series, and this time he comes face to face with the feared Donkey Lady!.